2011
DOI: 10.1007/s13197-011-0515-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wheat gluten hydrolysates as taste-active compounds with antioxidant activity

Abstract: Wheat gluten was subjected to enzymatic hydrolysis with various proteases (Alcalase, Flavourzyme, Protamex) and the taste-enhancing properties and antioxidant activities of the resulting wheat gluten hydrolysates (WGHs) were characterized. The contents of the hydrophobic amino acid of the WGHs were highly correlated with the degree of hydrolysis by Flavourzyme and Protamex, except Alcalase. The taste profiles of the Alcalase-treated WGHs showed decreased bitterness while umami and overall acceptability increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Koo et al () reported that the hydrophobic amino acids such as proline, glycine, alanine, valine, methionine, isoleucine, leucine, and phenylalanine increased when wheat was treated with Protamex to obtain a hydrolyzed product. In addition, the amino acids tryptophan, tyrosine, histidine, leucine, proline, and cysteine have been reported to exhibit antioxidant activities and ability to chelate metals (Chen, Muramoto, Yamauchi, & Nokihara, ; Park, Jung, Nam, Shahidi, & Kim, ), which could suggest that the increased antioxidant capacity of the hydrolyzates with respect to fresh bee‐pollen is partly due to the increase in free amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koo et al () reported that the hydrophobic amino acids such as proline, glycine, alanine, valine, methionine, isoleucine, leucine, and phenylalanine increased when wheat was treated with Protamex to obtain a hydrolyzed product. In addition, the amino acids tryptophan, tyrosine, histidine, leucine, proline, and cysteine have been reported to exhibit antioxidant activities and ability to chelate metals (Chen, Muramoto, Yamauchi, & Nokihara, ; Park, Jung, Nam, Shahidi, & Kim, ), which could suggest that the increased antioxidant capacity of the hydrolyzates with respect to fresh bee‐pollen is partly due to the increase in free amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with respect to the total protein content found by the Bradford method, where higher values for protein in hydrolyzates with proteases were found, compared to fresh bee-pollen. Koo et al (2014) reported that the hydrophobic amino acids such as proline, glycine, alanine, valine, methionine, isoleucine, leucine, and phenylalanine increased when wheat was treated with…”
Section: Nutritional and Bioactive Resultsmentioning
confidence: 99%
“…Wheat gluten hydrolysates (WGH), a mixture of amino acids and peptides, were found to have a wide range of bioactivities (Koo et al, 2014;Merz et al, 2015). Supplementation of WGH in fermentation medium could increase the FAN level and add the complexity of nitrogen source to ensure efficient yeast cell growth and fermentation, which was important to the successful completion of fermentation processes and the final product quality.…”
Section: Introductionmentioning
confidence: 99%
“…SHH used in this study was an enzymic hydrolysate, which is hydrolyzed by flavourzyme, a compound enzyme consisting of the incision enzyme and circumscribed enzyme. Treatment with flavourzyme effectively resects hydrophobic amino acids from the protein end [ 52 ]. The enzymic hydrolysate, SHH, could likely enhance their bioactivities and thus show a strong reduction of asthmatic parameters in OVA-challenged allergic asthma model.…”
Section: Discussionmentioning
confidence: 99%